2019
DOI: 10.1007/s10592-019-01183-3
|View full text |Cite
|
Sign up to set email alerts
|

Broad-scale patterns of genetic diversity and structure in a foundational salt marsh species black needlerush (Juncus roemerianus)

Abstract: Clonal and genetic diversity in foundational plant species are critical for species resiliency and ecosystem processes, both of which contribute to restoration success; however, genetic data is often lacking for common plant species used in many restoration practices. Only a few plant species dominate salt marshes, ecologically and economically valuable ecosystems targeted for restoration due to global decline. Despite being a foundational species in southeastern United States salt marshes black needlerush (Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Studies on native southeastern US S. alterniflora populations have reported diversity levels that are comparable to other outcrossing grasses, despite the fact that this species also spreads prolifically by clonal reproduction (Foust et al, 2016; Richards et al, 2004; Robertson et al, 2017; Zerebecki et al, 2021). Tumas et al (2019) found greater genetic diversity in Gulf of Mexico than Atlantic coast populations of the salt marsh dominant (potential foundation species) plant Juncus roemerianus , but like in R. mangle , measures of genetic diversity varied dramatically across the range. The authors suggest this could be the result of differences in plant community and disturbance regimes or reflect a relationship with population size.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on native southeastern US S. alterniflora populations have reported diversity levels that are comparable to other outcrossing grasses, despite the fact that this species also spreads prolifically by clonal reproduction (Foust et al, 2016; Richards et al, 2004; Robertson et al, 2017; Zerebecki et al, 2021). Tumas et al (2019) found greater genetic diversity in Gulf of Mexico than Atlantic coast populations of the salt marsh dominant (potential foundation species) plant Juncus roemerianus , but like in R. mangle , measures of genetic diversity varied dramatically across the range. The authors suggest this could be the result of differences in plant community and disturbance regimes or reflect a relationship with population size.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the genetic makeup of foundation plant species in particular, is important for conservation because these species create and define ecological communities and contribute disproportionately to ecosystem function (Ellison et al, 2005; Hughes and Lotterhos, 2014; Lau et al, 2016; Ellison, 2019; Whitham et al, 2020). Foundation grass species often combine clonal and sexual reproduction (Franks et al, 2004; Keeler, 2004; Richards et al, 2004; Tumas et al, 2019). Although our initial analysis found that every ramet of the grass L. chinensis was a unique genotype, further consideration of the reproductive biology of the species and the number and type of markers we used, suggested that we had 13 lineages that were closely associated with patches.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on another perennial grass Spartina alterniflora reported either that nearly every ramet was unique (Richards et al, 2004; Foust et al, 2016, Robertson et al, 2017) or that the number of ramets per genet varied greatly (Hughes and Lotterhos, 2014). Moreover, Tumas et al (2019) found that measures of genetic and clonal diversity varied dramatically across the range of the salt marsh foundation plant Juncus roemerianus . They found higher genetic diversity and lower clonal diversity in Gulf of Mexico populations than on the Atlantic coast.…”
Section: Discussionmentioning
confidence: 99%
“…Foundation grass species often combine clonal and sexual reproduction (Franks et al, 2004;Keeler et al, 2004;Richards et al, 2004;Tumas et al, 2019). Although our initial analysis found that every ramet of the foundation grass L. chinensis was a unique genotype, further consideration of the reproductive biology of the species and the number and type of markers we used, suggest that we have 13 lineages that are closely associated with patches and some small amount of variation that could be due to somatic mutation as well as technical or scoring errors, which requires further study to decipher.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on another perennial grass Spartina alterniflora reported either that nearly every ramet was unique (Richards et al, 2004;Foust et al, 2016, Robertson et al, 2017 or that the number of ramets per genet varied greatly (Hughes and Lotterhos, 2014). Moreover, Tumas et al (2019) found that measures of genetic and clonal diversity varied dramatically across the range of the salt marsh foundation plant Juncus roemerianus. They found greater genetic diversity and lower clonal diversity in Gulf of Mexico populations than on the Atlantic coast.…”
Section: Identifying Unique Genotypes -mentioning
confidence: 99%